Albendazole alone vs. albendazole and diethylcarbamazine combination therapy for trichuriasis - Nasution, Windya Sari; Ali, Muhammad; Pasaribu, Ayodhia Pitaloka; Pasaribu, Syahril; Lubis, Chairuddin P. (Paediatrica Indonesiana, 2014)
Background Trichuris trichiura is one of the most common soil-transmitted helminths, estimated to infect l billion people worldwide. Several studies have compared the efficacies of albendazole and diethylcarbamazine, but the efficacy of a combination of these two drugs has been inconclusive. Objective To assess the effectiveness of a single dose of albendazole compared to a combination of albendazole and diethylcarbamazine for trichuriasis treatment. Methods A randomized, clinical open trial was conducted from June to September 2009 on elementary school children with trichuriasis from two villages in the North Sumatera Province. Stool specimens were collected at baseline and at days 7, 14, 21, and 28 after treatment, and examined by the Kato Katz method. Subjects were randomized into two groups. Group I received a single dose of albendazole (400 mg) and group II received albendazole (400 mg) plus diethylcarbamazine (6 mg! kg). Statistical analyses used were Chi square test for cure rates and Wilcoxon rank test for egg reduction rates. Results One hundred eight children were enrolled and randomized into group l (53 children) and group II (55 children). The prevalence of T. trichiura infection was 54.7%. There were no significant differences (P=0.52) in the cure rate between groups I and II (66% and 60%, respectively) or in egg reduction rates at day 28 (54.5% and 60.07%, respectively, P= 0.10). Conclusion Albendazole alone and abendazole combined with diethylcarbamazine have similar efficacies for trichuriasis treatment, in terms of cure rates and egg reduction rates.